2019
DOI: 10.1111/maps.13249
|View full text |Cite
|
Sign up to set email alerts
|

Petrological, petrofabric, and oxygen isotopic study of five ungrouped meteorites related to brachinites

Abstract: Northwest Africa (NWA) 6112, Miller Range (MIL) 090206 (plus its pairs: MIL 090340 and MIL 090405), and Divnoe are olivine‐rich ungrouped achondrites. We investigated and compared their petrography, mineralogy, and olivine fabrics. We additionally measured the oxygen isotopic compositions of NWA 6112. They show similar petrography, mineralogy, and oxygen isotopic compositions and we concluded that these five meteorites are brachinite clan meteorites. We found that NWA 6112 and Divnoe had a c axis concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…The mineralogical assemblage occurring in Al Huwaysah 010 is a widespread fine-grained assemblage where opaque phases are associated with Ca-poor orthopyroxene. This texture is similar to that observed in Divnoe, NWA 6112, MIL 090206, MIL 090304, MIL 090405, and other brachinite/brachinite-like meteorites, where opaque phases occurring in the fine-grained assemblage along with orthopyroxene are mainly represented by Fe-sulfide and Fe-Ni metal (Goodrich et al, 2011(Goodrich et al, , 2017Hasegawa et al, 2019;Irving et al, 2013;Rumble III et al, 2008). Moreover, in Al Huwaysah 010, almost all olivine-olivine, olivine-augite, and olivine-chromite grain boundaries are lined with such fine-grained assemblages and they also occur as patches within olivine (Figure 2) and even in olivine chadacrysts enclosed in Ca-rich clinopyroxene (Figure 1b).…”
Section: Petrography Mineralogy and Mineral Chemistry: A Comparison W...supporting
confidence: 81%
See 2 more Smart Citations
“…The mineralogical assemblage occurring in Al Huwaysah 010 is a widespread fine-grained assemblage where opaque phases are associated with Ca-poor orthopyroxene. This texture is similar to that observed in Divnoe, NWA 6112, MIL 090206, MIL 090304, MIL 090405, and other brachinite/brachinite-like meteorites, where opaque phases occurring in the fine-grained assemblage along with orthopyroxene are mainly represented by Fe-sulfide and Fe-Ni metal (Goodrich et al, 2011(Goodrich et al, , 2017Hasegawa et al, 2019;Irving et al, 2013;Rumble III et al, 2008). Moreover, in Al Huwaysah 010, almost all olivine-olivine, olivine-augite, and olivine-chromite grain boundaries are lined with such fine-grained assemblages and they also occur as patches within olivine (Figure 2) and even in olivine chadacrysts enclosed in Ca-rich clinopyroxene (Figure 1b).…”
Section: Petrography Mineralogy and Mineral Chemistry: A Comparison W...supporting
confidence: 81%
“…Olivine in Al Huwaysah 010 (Table 1) has a higher amount of Mg (Fo 83.3 ) compared to all the known brachinites, where the composition usually ranges from Fo 64 to Fo 70 . These differences, however, become less pronounced when specific brachinites (or brachinite‐like achondrites) are considered where olivine ranges from Fo 72 to Fo 80 (Crossley et al., 2020; Goodrich et al., 2011; Greenwood et al., 2017; Hasegawa et al., 2019; Irving et al., 2013). A clear difference may also be observed between the value of molar Fe/Mn (29.4) in olivine of Al Huwaysah 010 and those of other brachinites (52–77).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the samples are classified as ungrouped achondrites (NWA 6112, NWA 5363, NWA 1058), but their chemical and petrologic properties suggest they may be linked to brachinites. Accordingly, these meteorites are sometimes also classified as 'brachinite-like' meteorites (Day et al, 2012;Hasegawa et al, 2019).…”
Section: Samples and Sample Preparationmentioning
confidence: 99%
“…for samples with N>3. c NWA 6112 is petrologically similar to brachinites, however, based on the Fa composition slightly outside the range of brachinite and hence classified as ungrouped achondrite. Recently,Hasegawa et al (2019) re-investigated oxygen isotopes, petrography, mineralogy, and olivine fabric of NWA 6112 and concluded that the sample belongs to the brachinite clan meteorites.…”
mentioning
confidence: 99%